2020
DOI: 10.1093/infdis/jiaa093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emodin on Coxsackievirus B3m-Mediated Encephalitis in Hand, Foot, and Mouth Disease by Inhibiting Toll-Like Receptor 3 Pathway In Vitro and In Vivo

Abstract: Abstract Background Encephalitis in hand, foot, and mouth disease (HFMD) is a serious threat to children’s health and life. Toll-like receptor 3 (TLR3) is an innate immune-recognition receptor that can recognize virus and initiate innate immune responses. Emodin has the effects of anti-inflammatory and regulating immune function, but the mechanism is not very clear. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
16
2
Order By: Relevance
“…essential for the injury and necrosis of cardiovascular cells (Ait-Oufella et al, 2019). Emodin has been found to have effective antiinflammatory effects (Shrimali et al, 2013;Ding et al, 2020), and it also has the activity in cardiovascular diseases. It is reported that emodin can control the expression and secretion of inflammatory factors by inhibiting the transcription factor nuclear factor kappa-B (NF-kB) in a variety of inflammatory diseases.…”
Section: Targets and Studies Of Emodin Against Anti-cardiovascular DImentioning
confidence: 99%
“…essential for the injury and necrosis of cardiovascular cells (Ait-Oufella et al, 2019). Emodin has been found to have effective antiinflammatory effects (Shrimali et al, 2013;Ding et al, 2020), and it also has the activity in cardiovascular diseases. It is reported that emodin can control the expression and secretion of inflammatory factors by inhibiting the transcription factor nuclear factor kappa-B (NF-kB) in a variety of inflammatory diseases.…”
Section: Targets and Studies Of Emodin Against Anti-cardiovascular DImentioning
confidence: 99%
“…In the present study, we found that the mRNA expression of TLR3 was induced by Emodin in iPAMs after PRRSV infection. On the contrary, Emodin could decrease the mRNA and protein levels of TLR3 and downstream molecules against Coxsackievirus B3m infection [ 25 ], indicating that Emodin has different antiviral mechanisms involved in fighting different virus infections. After recognition of viral nucleic acids, TLRs could recruit downstream kinases that phosphorylate downstream adaptor proteins to relay signals to activate transcription factors IFN regulatory factor 3 (IRF3) and IRF7, which are mainly involved in IFN gene induction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emodin (1, 3, 8-trihydroxy-6-methylanthraquinone) is a derived anthraquinone compound isolated from roots and barks of pharmaceutical plants, including Rheum palmatum and Aloe vera [ 23 ]. It has been reported that Emodin has a significant inhibitory effect on Cyprinid herpesvirus 3 [ 24 ], Coxsackieviruses [ 25 , 26 , 27 ], Zika virus [ 28 ], Enterovirus 71 [ 29 ], Epstein-Barr virus [ 30 ], HCoV-OC43 [ 31 ], Herpes simplex virus [ 32 , 33 ], Hepatitis B virus [ 34 ] and SARS-CoV [ 35 ]. The antiviral activity of Emodin achieved by blocking the virus-receptor interaction [ 35 ], inhibiting viral protein translation [ 26 ], viral maturation [ 29 ], and viral release [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Toll-like receptors (TLRs) are an important class of protein molecules involved in nonspecific immunity that can recognize the conserved structure of biomolecules derived from microorganisms and induce antimicrobial immune responses. 5 After identifying the pathogens, TLRs can activate a variety of signaling pathways, including downstream MyD88-independent and MyD88-dependent pathways, which regulate the expression of a range of inflammatory cytokines and participate in inflammation and immune responses. 6 As pattern recognition receptors, TLRs can not only sense pathogenassociated molecular patterns (PAMPs) but also perceive damagerelated molecular patterns (DAMPs), showing the similarity between pathogenic and non-pathogenic inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Toll‐like receptors (TLRs) are an important class of protein molecules involved in nonspecific immunity that can recognize the conserved structure of biomolecules derived from microorganisms and induce antimicrobial immune responses 5 . After identifying the pathogens, TLRs can activate a variety of signaling pathways, including downstream MyD88‐independent and MyD88‐dependent pathways, which regulate the expression of a range of inflammatory cytokines and participate in inflammation and immune responses 6 .…”
Section: Introductionmentioning
confidence: 99%